Production of recombinant human xCT (SLC7A11) and reconstitution in proteoliposomes for functional studies - Galluccio, Michele; Scalise, Mariafrancesca; Pappacoda, Gilda; Scarpelli, Martina; Bonanomi, Marcella; Gaglio, Daniela; Indiveri, Cesare (Frontiers in Physiology, 2022)
The plasma membrane transporter xCT belongs to the SLC7 family and has the physiological role of mediating the exchange of glutamate and cystine across the cell plasma membrane, being crucial for redox control. The xCT protein forms a heterodimer with the ancillary protein CD98. Over the years, xCT became a hot pharmacological target due to the documented over-expression in virtually all human cancers, which rely on cystine availability for their progression. Notwithstanding, several unknown aspects of xCT biology still exist that require a suitable single protein experimental model, to be addressed. To this aim, the recombinant host Escherichia coli has been exploited to over-express the human isoform of xCT. In this widely used and low-cost system, the optimization for growth and protein production has been achieved by acting on the metabolic needs of the bacterial strains. Then, the His-tagged protein has been purified by Ni2+-chelating chromatography and reconstituted in proteoliposomes for transport activity assays. The expressed protein was in a folded/active state allowing functional and kinetic characterization. Interestingly, the features of the recombinant protein meet those of the native one extracted from intact cells, further confirming the suitability of E. coli as a host for the expression of human proteins. This study opens perspectives for elucidating other molecular aspects of xCT, as well as for studying the interaction with endogenous and exogenous compounds, relevant to human health.